Produção de meios filtrantes para ar a base de isopor reciclado utilizando a técnica de eletrofiação: avaliação de variáveis de processo e incorporação de surfactantes - Ventin, Luis Augusto Fernandez (Universidade Federal de São Carlos, 2025)
Air quality and reuse of plastic waste are two problems that have challenged humanity and the terrestrial ecosystem. Expanded polystyrene (PS-E) can be recycled to produce air filtering media to, simultaneously, address these two problems. Thus, this work had as objective to develop air filters from recycled PS-E produced via electrospinning. Process variables such as polymer concentration, spinning time, type of collecting substrate, and the addition or not of ionic surfactants were investigated. The influence of the collecting substrate on the formation of nanofibers was observed, the nylon mesh resulted in a reduced area of fiber deposition and incomplete evaporation of solvent. Samples spun on steel mesh maintained surface electric potential (TES) even after 30 days, while those electrospun on copper mesh have their surface voltage completely dissipated after 7 days. An atypical phenomenon was observed in some samples that presented momentary increase of TES, possibly related to the surface redistribution of charges. Electret filters presented overall efficiencies higher than 90% for particles with average diameter of 0.25 μm (MP0,25), with quality factors (QFs) varying between 0.035 and 0.064 Pa⁻¹. However, after electrostatic discharge, the overall efficiency was reduced to values between 52.26% and 76.89%, and the QF decreased to the range of 0.008 to 0.024 Pa⁻¹. The polarity of the voltage applied during electrospinning does not appear to have effect on the collection efficiency, but affects the morphology of the fibers, with the samples of negative polarity presenting greater occurrence of structural defects. The addition of ionic surfactants cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS) resulted in absence of TES (0 kV), indicating that the increase of the conductivity of the solution facilitated the escape of the charges. Despite the absence of the electret character, these filters exhibited high collection efficiency, higher than 99.2% for MP0,25. Moreover, the formation of self-assembling fibrous stacking as well as the presence of electrowebs was observed. These results contribute to the understanding of production of electret filters and reinforce the possibility of employment of recycled PS-E as raw material for the production of air filtering media.
Production of recycled expanded polystyrene-based air filter media via electrospinning: evaluation of process variables and incorporation of surfactants
Keywords: Eletrofiação; Polaridade; Eletretos; Nanofibras; Filtração; Electrospinning; Polarity; Electrets; Nanofibers; Filtration; ENGENHARIAS::ENGENHARIA QUIMICA; 13. Ação contra a Mudança Global do Clima; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis